Perception of an electronic portfolio in a surgical oncology course: A pilot study - Díaz-Plasencia, Juan A.; Valencia-Mariñas, Hugo D.; Lozano Peralta, Katherine Y. (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
The present study evaluates the acceptability of an electronic portfolio model of virtual, linear, and integrative clinical cases, their perception of the flipped classroom methodology, and modified team learning. The mixed teaching model of the electronic portfolio flipped classroom and modified team learning for undergraduate students allowed to improve student satisfaction by promoting active and reflective learning. Students found the valuable model for a variety of purposes in their clinical science education in the period of the COVID-19 pandemic outbreak.